A new species, Dactylosoma piperis n. sp. (Apicomplexa, Dactylosomatidae), from the pepper frog Leptodactylus labyrinthicus (Anura, Leptodactylidae) from Mato Grosso State, Brazil. - Úngari, Letícia Pereira [UNESP]; Netherlands, Edward Charles; Quagliatto Santos, André Luiz; Alcantara, Edna Paulino De [UNESP]; Emmerich, Enzo [UNESP]; Da Silva, Reinaldo José [UNESP]; O'Dwyer, Lucia Helena [UNESP] (EDP Sciences, 2020)
The Dactylosomatidae Jakowska and Negrelli, 1955 are one of four families belonging to adeleorinid coccidia and comprise the genera Babesiosoma Jakowska and Nigrelli, 1956 and Dactylosoma Labbé, 1894. These blood protozoa occur in peripheral blood of lower vertebrates, and are commonly reported parasitising amphibians. The present study describes Dactylosoma piperis n. sp. from the pepper frog Leptodactylus labyrinthicus (Spix, 1824) (Anura: Leptodactylidae), collected in 2018 at the municipality of Araguaiana, Mato Grosso State, Brazil, based on morphology of intra-erythrocytic trophozoite, primary and secondary merogonic stages and a molecular analysis (partial 18S rDNA). Dactylosoma piperis n. sp. forms a well-supported clade with other Dactylosomatidae. This is the first molecular characterization of a species of Dactylosoma from a Brazilian anuran.
Keywords: 18S rRNA; Amphibian; Haemogregarine; Haemoparasite; Phylogeny